The Political Economy of Trade Barriers in Peru - Tello Pacheco, Mario (Universidad Pedagógica y Tecnológica de Colombia, 2022)
This paper analyzes the political economy factors and actors that may have influenced trade instruments in Peru during the liberalization period of 2001-2015 (which started in 1990 under Fujimori’s administration). The evidence supports the hypothesis that Peruvian trade barriers liberalization in period 2000-2015 was led by the powerful “Ministry of Economy and Finance (MEF)”, accompanied by traditional and diversified exporters (that consolidated the unilateral trade liberalization) and by import substitution firms that influenced to some degree, and slowed down the rate of liberalization of unilateral trade barriers. In addition, the unilateral trade liberalization was facilitated by the weak role of the formal labor force and liberal-oriented consumer interest groups.